2021
DOI: 10.3389/fimmu.2021.636013
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Receptor-6 Promotes B-1 Cell Trafficking to Perivascular Adipose Tissue, Local IgM Production and Atheroprotection

Abstract: Chemokine receptor-6 (CCR6) mediates immune cell recruitment to inflammatory sites and has cell type-specific effects on diet-induced atherosclerosis in mice. Previously we showed that loss of CCR6 in B cells resulted in loss of B cell-mediated atheroprotection, although the B cell subtype mediating this effect was unknown. Perivascular adipose tissue (PVAT) harbors high numbers of B cells including atheroprotective IgM secreting B-1 cells. Production of IgM antibodies is a major mechanism whereby B-1 cells li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Chemokine/chemokine receptors interactions is a major mechanism regulating trafficking of immune cells throughout the body and CCR6 has been shown to regulate B-1 cell mediated atheroprotection in mice (28). In this present study, we found that B-1b cells express significantly more CCR6 than B-1a cells and that CCR6 regulates B-1b cell recruitment to the spleen.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Chemokine/chemokine receptors interactions is a major mechanism regulating trafficking of immune cells throughout the body and CCR6 has been shown to regulate B-1 cell mediated atheroprotection in mice (28). In this present study, we found that B-1b cells express significantly more CCR6 than B-1a cells and that CCR6 regulates B-1b cell recruitment to the spleen.…”
Section: Discussionsupporting
confidence: 59%
“…Notably, canonical pathway analysis showed that, B-1b cells express genes that are involved in CCR6 signaling pathway (Figure 2B). Our recent study demonstrated that CCR6 is highly expressed on splenic total B-1 cells compared to total B-1 cells from PerC (28). Since B-1b cells express high levels of CCR6, this CCR6 may regulate the recruitment of B-1b cells to the spleen.…”
Section: Chemokine Receptor-6 Regulates B-1b Cell Migration To Spleenmentioning
confidence: 95%
“…As α-gal IgE sensitization has been shown to associate with CAD ( 6 , 7 ), we further explored roles of CCR6 and CXCR4 in cardiovascular disease. Upadhye et al and Srikakulapu et al had previously investigated roles of CCR6 and CXCR4 on B cells in contributing to atherosclerosis ( 33 , 34 ). However, those studies focused on atheroprotective B-1 cells and the role of CCR6 and CXCR4 in boosting anti-inflammatory IgM production.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a decrease in the number of B-1 cells that secrete antiatherosclerotic IgM in ApoE −/− mouse PVAT. This further worsens the atherosclerotic lesion formation in the mouse coronary artery and aorta [ 107 ]. Additionally, microRNA-19b in endothelial cell-derived microparticles promotes atherosclerosis progression in ApoE −/− mice by increasing the secretion of proinflammatory cytokines (IL-6, IL-10, and TNF- α ) and inducing macrophage infiltration in PVAT [ 108 ].…”
Section: Pvat Inflammation In Vascular Diseasesmentioning
confidence: 99%